Enhancing the knowledge and skills of smallholders to adopt market-oriented tree management practices: lessons from Master TreeGrower training courses in Indonesia - Muktasam, A.; Reid, R.; Race, D.; Wakka, A.K.; Oktalina, S.N.; Agusman; Herawati, T.; Bisjoe, A.R.H. (Informa UK Limited, 2019)
Growing trees on farmland continues to be a promising land-use option for smallholders in Indonesia as they look to diversify their enterprises beyond the main agricultural sector. While most smallholders integrate trees into their farming systems, selling timber and other tree products has usually been infrequent and opportunistic. Because of this infrequent trade, most smallholders rarely adopt silvicultural practices that would increase the commercial value of their trees. A research project trialled an alternative approach to forestry extension in Indonesia, known as the Master TreeGrower (MTG) training course. The MTG training courses used a farmer-centred approach to teach smallholders about forest science and took participants to market hubs so they could better understand how different forest products were valued by traders. The MTG training approach was trialled in 2014 in five districts in Indonesia and involved 118 smallholders and 27 non-farmers as course participants. This article reports on a recent evaluation of the MTG training courses held about three years earlier to explore the enduring impacts of the training approach and whether it can be scaled-out to other areas of Indonesia. The evaluation data were collected via focus group discussions (FGDs), in-depth interviews, household surveys and observations at three project sites: Pati (Central Java), Gunungkidul (Yogyakarta) and Bulukumba (South Sulawesi). A questionnaire was distributed among the participants of the FGDs to assess the extent different knowledge and skills of tree management that had been adopted by them following the MTG courses. The evaluation of the MTG approach revealed that the courses were effective in increasing smallholders' knowledge of commercial forestry and their silvicultural skills. Many participants were more active with silviculture and planned to invest further in commercial forestry following the MTG training. In effect, the MTG training appeared to change the hearts and minds of the farmers about how commercial forestry could enhance their livelihoods.